Reliability assessment and enhancement of Dangila distribution system with distribution generation. Issue 1 (31st December 2023) - Mamo, Addisu; Hizkiel, Abraham
Abstract: The reliability assessment helps to determine the existing power system reliability. Equipment failures may decrease reliability and the major contributory factors for power system unreliability. Therefore, the objective of this study was reliability assessment for distribution with distribution generation units and without distribution generation units, Dangila substation from 2020 to 2021. The base case reliability indices were 774.93, 1231.48, 1.589, 85.96%, and 14.04 for system average interruption frequency index, system average interruption duration index, customer average interruption duration index, average service availability index and average service unavailability index respectively. These indices are below the standards of Ethiopian Electric power set indices values of 20 system average interruption frequency index and 25 system average interruption duration index. Therefore, the system needs improvement to achieve the minimum system reliability standard. Distribution generation was used to improve the system reliability in this paper. Distribution generation was placed at five suggested locations of feeder seven from substation, 66kilometer, 80kilometer, 100kilometer, 113.3kilometer, and 146kilometer distances. The results shows that as distribution generation was placed further from Supply point the reliability of the power system will be improved more. The assessment result of feeder seven shows that the feeder had more outages with the base cases of 636, 833, and 1.311 system average interruption frequency index, system average interruption duration index, customer average interruption duration index respectively. The size of distribution generation for feeder seven was 3.13 MW to supply 50% of feeder peak load. After distribution generation placed at feeder seven the system average interruption frequency index, system average interruption duration index, customer average interruption duration index, and average service unavailability index indices were 20.0868, 25.109, 1.25, and 99.71%. This shows that the system reliability is improved as compared to the base case and the reliability standards of the country were achieved.